Studi Peningkatan Mutu Biobriket dengan Penambahan Paper Waste dan Minyak Jelantah - Mohamad Mirwan; Nova Ariyanti (Prosiding ESEC, 2022)
Waste processing that is less than optimal causes the generation of large amounts of waste so that action is needed to process it into useful new products, for example into briquettes. The implementation of adding raw materials in making briquettes with waste that has low economic value is expected to improve the quality of briquettes. Paper waste and used cooking oil have the potential to be processed as additional raw materials in the manufacture of briquettes in producing alternative fuels. Based on the results of characteristic testing, the quality of the briquettes increased after the addition of paper waste and used cooking oil. The water content of briquettes from 5,12% decreased to 1 – 2%. The ash content of briquettes from 10,01% decreased to 5 – 7%. The calorific value of briquettes from 4902 cal/g increased to 5200 – 5700 cal/g. The compressive strength of briquettes from 4,38 kg/cm2 increased to 5,51 – 9,48 kg/cm2. The immersion treatment of used cooking oil has an optimum time limit because it can affect the solidity of the charcoal when testing the compressive strength. The addition of paper waste and used cooking oil to the combustion rate increases the combustion power of briquettes and the flame lasts longer so that the combustion rate range obtained is small. The emission of carbon monoxide (CO) produced by the briquettes in this study is relatively low because it is still far below the required quality standards.